Development of Digital LKPD with a Scientific Approach to Mushroom Materials for High School Students Class X - Arief Widiyantoro; Hani Irawati (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
This study aims to evaluate the quality of the digital student activity sheet (LKPD) focused on mushroom materials, as assessed by experts and teachers; to gather students' responses to the digital LKPD utilizing a scientific approach; and to assess the overall feasibility of this digital KTPD in enhancing the learning process related to mushroom materials. This research has been carried out in the form of a 4-D development model. The evaluation of material experts received a percentage of 88.02% with a very good category, so this teaching material is suitable for use as a class x teaching material for mushroom material. The average of the small group test and the large group test was declared very good. The feasibility aspect of the scientific approach received 95.00% with the category of very good and the aspect of ability received 85.00%. The long-term impact study could measure knowledge retention, engagement, and application of concepts over time. This study could explore the potential for cross-curricular connections, particularly with environmental science or technology, to enhance students' understanding of fungal materials and their applications.